2006
DOI: 10.1039/b610690k
|View full text |Cite
|
Sign up to set email alerts
|

5-endo Heck-type cyclization of 2-(trifluoromethyl)allyl ketone oximes: synthesis of 4-difluoromethylene-substituted 1-pyrrolines

Abstract: 2-(Trifluoromethyl)allyl ketone O-pentafluorobenzoyloximes undergo a palladium-catalyzed 5-endo mode of alkene insertion via oxidative addition of the N-O bond, followed by beta-fluorine elimination to produce 4-difluoromethylene-1-pyrrolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…[51] The formation of exo -difluoromethylene product has been attributed to the β-F elimination (instead of β-H elimination) from alkyl-Pd II intermediate.…”
Section: Aza-heckmentioning
confidence: 99%
“…[51] The formation of exo -difluoromethylene product has been attributed to the β-F elimination (instead of β-H elimination) from alkyl-Pd II intermediate.…”
Section: Aza-heckmentioning
confidence: 99%
“…The products were employed to probe the effect of fluorine substitution on the molecular properties and on the arrangement of molecules in the solid state [81]. The absorption spectroscopy showed that 124 and 126 had a λmax at approximately 350 nm, and addition of dimethylaniline to the hexane solutions led to exciplex emission with λmax ranging from 458 to 514 Furthermore, Pd-catalyzed Heck-type cyclization of 2-trifluoromethyl-1-alkenes (118) bearing an O-acyloxime moiety was accomplished (Scheme 23) [45,80]. The reaction represented a rare example of 5-endo mode alkene insertion into transition-metal species via oxidative addition of the N-O bond (119).…”
Section: Other Fluorine-containing Alkenes As the Cross-coupling Reagmentioning
confidence: 99%
“…The wide range of substrates and the good functional group tolerance made this strategy facile and practical for the streamlined synthesis of functional styrenes. Furthermore, Pd-catalyzed Heck-type cyclization of 2-trifluoromethyl-1-alkenes (118) bearing an O-acyloxime moiety was accomplished (Scheme 23) [45,80]. The reaction represented a rare example of 5-endo mode alkene insertion into transition-metal species via oxidative addition of the N-O bond (119).…”
Section: Scheme 17 Preparation Of Diazonium-functionalized Oligo(phementioning
confidence: 99%
See 1 more Smart Citation
“…[4] Both substitutions have been useful in organic syntheses. [5][6][7][8][9] On the basis of the concept of combining these two substitutions, we adopted a simple method of constructing fluorinated ring systems using bifunctional nucleophiles (XH-YH, Scheme 1 C). In the proposed ring constructions, S N 2'type reactions of 2-trifluoromethyl-1-alkenes would proceed with one of the nucleophilic centers (XH-) to give the corresponding 1,1-difluoro-1-alkenes, and the 1,1-difluoro-1alkenes formed would then be subjected to intramolecular S N V reactions with the other nucleophilic moiety (-YH), to give ring-fluorinated cyclic compounds.…”
mentioning
confidence: 99%